Pengaruh Kedisiplinan Diri dan Burnout (Thīna-Middha) terhadap Partisipasi Aktif dalam Kegiatan Keagamaan Remaja Buddhis Usia 15–18 Tahun di Jawa Tengah - Tri Setya Damayanti (Jurnal Budi Pekerti Agama Buddha, 2025)
This study aims to analyze the influence of self-discipline and burnout (Thīna-Middha) on active participation in religious activities among Buddhist adolescents aged 15–18 in Central Java. The approach used is quantitative with a survey method, and the sampling technique is cluster sampling. The instrument used is a semantic differential scale questionnaire to measure self-discipline, burnout, and active participation. Data analysis is performed using multiple linear regression to determine the influence of each variable on active participation. The results show that self-discipline has a positive and significant effect on active participation in Buddhist religious activities, while burnout has a negative and significant effect. These two variables contribute 41.1% to active participation in religious activities. These findings highlight the importance of self-discipline as a factor that drives active participation, as well as the negative impact of burnout on adolescents' involvement in religious activities. The implications of this study can be used as a basis for designing more effective and targeted programs for Buddhist adolescents, considering the factors of self-discipline and efforts to mitigate burnout. These programs need to be tailored to the spiritual and psychological needs of adolescents to enhance their active participation in religious activities.